The impact of marketing automation software on international marketing efficiency - Tiitola, Roosa (My University, 2022)
Globalization and growing competition in global markets have increased the need for effective international marketing strategies. Digital transformation is accelerating the shift from traditional marketing towards digital marketing, and marketers are becoming more and more dependent on the increasing amount of real-time data available online. This has also caused the growing need for marketing automation, which removes the need for manual work and helps with collecting, handling, and analysing marketing data. Marketing automation software enable several benefits for companies, but the implementation and use of the software creates various challenges that need to be first tackled. The goal of the study is to understand the impact that marketing automation software have on international marketing efficiency. The theoretical background of the study consists of analysing international marketing strategies and marketing automation software’s benefits and challenges as a part of international marketing. The framework of the study consists of seven antecedent factors that determine marketing automation’s success. The seven factors are review and development of internal marketing and business processes, scoping of instance requirements and implementation project, gain organization buy-in and find a project champion, create and deliver relevant and timely content, set realistic expectations and be patient, continue to invest and reallocate found efficiencies, and correct human resources. The study was conducted as qualitative research, where the data was collected from seven participants as a form of semi-structured interviews. The findings of the study show that the impact of marketing automation software on international marketing efficiency is dependent on all the seven antecedent factors. Companies use marketing automation software for different purposes, and the benefits also vary based on how the software is used. The common benefits regardless of how the software is used are saving time, sending real-time content to the target audience, and quicker responses to customers. The benefits were relatively easy to measure, but the total impact of marketing automation software on international marketing was seen as difficult to measure and the study suggests that some companies might even avoid measuring it to avoid discovering the negative impacts of it. The impact of marketing automation software was also dependent on how much adaptation is needed locally.

Globalisaatio yhdessä kasvavan kilpailun kanssa ovat kasvattaneet tarvetta tehokkailla kansainvälisille markkinointistrategioille globaaleilla markkinoilla. Digitaalinen transformaatio kiihdyttää muutosta perinteisestä markkinoinnista kohti digitaalista markkinointia ja markkinoijat ovat koko ajan enemmän ja enemmän riippuvaisia kasvavasta määrästä reaaliaikaista dataa, joka on saatavilla verkosta. Tämä on myös kasvattanut tarvetta markkinoinnin automaatiolle, mikä poistaa tarvetta manuaaliselle työlle ja auttaa keräämään, käsittelemään ja analysoimaan markkinointidataa. Markkinoinnin automaatio-ohjelmistot tuovat yrityksille useita hyötyjä, mutta ohjelmiston käyttöönotto sekä käyttö luovat erilaisia haasteita, jotka on ensin ratkottava. Tutkimuksen tarkoitus on ymmärtää markkinoinnin automaatio-ohjelmistojen vaikutus kansainvälisen markkinoinnin tehokkuuteen. Tutkimuksen teoreettinen tausta koostuu kansainvälisten markkinointistrategioiden analysoinnista sekä markkinoinnin automaatio-ohjelmistojen hyötyjen ja haittojen määrittämisestä kansainväliselle markkinoinnille. Tutkimuksen viitekehys koostuu seitsemästä edellytystekijästä, jotka määrittävät markkinoinnin automaation menestyksen. Tutkimus tehtiin kvalitatiivisena tutkimuksena, jossa aineisto kerättiin seitsemältä osallistujalta puolistrukturoitujen haastattelujen muodossa. Tutkimuksen tulokset osoittavat, että markkinoinnin automaatio-ohjelmistojen vaikutus kansainvälisen markkinoinnin tehokkuuteen on riippuvainen kaikista seitsemästä edellytystekijästä. Yritykset käyttävät markkinoinnin automaatio-ohjelmistoja eri tarkoituksiin ja hyödyt vaihtelevat riippuen siitä miten ohjelmistoa käytetään. Riippumatta siitä miten ohjelmistoa käytetään, yleiset hyödyt ovat ajansäästö, reaaliaikaisen sisällön lähetys kohdeyleisölle sekä nopeammat vastaukset asiakkaille. Hyötyjä oli suhteellisen helppo mitata, mutta markkinoinnin automaatio-ohjelmistojen kokonaisvaikutuksen mittaaminen kansainväliselle markkinoinnille nähtiin vaikeana mitata ja tutkimus osoittaa, että osa yrityksistä saattaa jopa vältellä sen mittausta välttyäkseen negatiivisten vaikutusten löytämiseltä. Markkinoinnin automaatio-ohjelmistojen vaikutus oli myös riippuvainen siitä, miten paljon adaptaatiota tarvitaan paikallisesti.
Keywords: marketing; automation; international market; digital marketing; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business